Agro-processing, food prices, and COVID-19: The case of rice mills in Myanmar - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
This assesses the impacts of COVID-19 on the processing sector of Myanmar’s agri-food system. We focus on the milling of rice, Myanmar’s most important staple, which accounts for more than half of calories consumed and serves as one of the country’s leading export commodities. Using unique data collected from telephone surveys with more than 400 medium- and large-scale rice mils, we highlight the major disruptions caused by the pandemic.